Factors Motivating Farmers for Collective Action for Management of Irrigation System in Nepal - Khanal, Kapil; Adhikari, Kalika Bahadur; Dhakal, Shiva Chandra; Marahatta, Santosh (International Journal of Social Sciences and Management, 2021)
The study analyzed the factors motivating the farmers for collective action for the management of the Shardikhola Puranchaur Irrigation System of the Kaski district of Nepal in 2019. A cross-sectional data of 184 farmers were collected using a simple random sampling method. A logit regression was used for data analysis. Age of the household head, years of schooling of the household head, presence of fine in monetary terms, number of farmers in a branch of the irrigation system positively motivated farmers in the involvement in the group for the management of the irrigation system. Motivation among farmers for collective action for management of the irrigation system was influenced by a combination of different factors. Therefore, the proper distribution of water at different branches, binding every level of users by law and transparency in the use of the income of the irrigation system must be maintained to achieve the desired results. Int. J. Soc. Sc. Manage. Vol. 8, Issue-1: 285-291